Change and Development of News Communication in China - Meng Ziyan (SHS Web of Conferences)
This paper discusses the change and development of the field of news dissemination in China, focusing on the far-reaching impact of technological progress, policy adjustments and changes in social demand on news dissemination. With the rapid development of the Internet and mobile communication technology, the form of news dissemination has undergone a fundamental change, gradually shifting from traditional media to new media. This transformation has not only changed the way of information production and dissemination, but also reshaped the audience’s habits of acquiring and consuming information. By systematically analysing these changes and developments, this paper reveals the important impacts of technological advancement drives, policy adjustments and changes in social demands on the development of news dissemination in China, which have promoted the speed and breadth of information dissemination, changed the way of news production, and allowed for increased audience participation, but also intensified media competition. It aims to provide reference for related research and useful insights for news communicators in practice.